Arboreal arthropod communities of remnant podocarp-hardwood rainforest, North Island, New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University - McWilliam, Hamish Andrew (Massey University, 1996)
Arthropod communities in the canopies of three species of native tree (Metrosideros robusta, Podocarpus totara, and Beilschmiedia tawa) were studied in three small lowland reserves of podocarp-hardwood forest in the Manawatu-Wanganui Region, New Zealand. The communities were sampled continuously from June 1994 to May 1995 using 18 flight-interception traps which were cleared monthly. Overall, 13 929 individuals from 863 morpho-species and 21 arthropod orders were captured. The number of species and individuals was highest in mid-summer with both variables strongly correlated with maximum air temperature. Arboreal arthropod communities of the smallest, most isolated forest reserve had the lowest overall diversity and species equitability. B. tawa had the lowest abundance and diversity of arthropods of all three tree species examined possibly because the narrow, flexible leaves of this tree make it an unsuitable habitat for arthropods to live or alight upon. Diptera made up 34% of the total number of arthropods captured, while Coleoptera contributed 12% and Araneae 11% to the total catch. The relative abundance and species richness of Diptera peaked in spring, Coleoptera in summer and Araneae in autumn. Multivariate analysis of overall community structure suggests that season is the dominant determinant of community structure in the arthropod communities of these forest patches whereas site and tree species have minor effects. Given the large number of morpho-species collected, the conservation value of small forest patches for forest dwelling arthropods in New Zealand should not be underestimated.
Keywords: New Zealand -- North Island; Arthropod populations; Arthropoda; Rain forest animals